Acute myocardial infarction associated with the induction of general anesthesia - Küçük, Murathan; Korucuk, Necmettin; Tosun, Veysel; Ertuğrul, Fatma; Yıldırım, Aytül Belgi (The European Research Journal, 2018)
Perioperative acute myocardial infarction (AMI) is the most common cause of postoperative morbidity and mortality. It is a rare but important and fatal complication. Recognizing this situation may be difficult due to the influence of general anesthesia. Early diagnosis and treatment can decrease the morbidity and mortality of this fatal complication. In this case we present a 56-year-old female planned nephrectomy. After induction of general anesthesia acute inferoposterior myocardial infarction occurred and coronary angiograhy showed the proximal portion of the circumflex coronary artery (Cx) was occluded by thrombus, the left anterior descending coronary artery and the right coronary artery were plaque. Percutaneous transluminal coronary angioplasty and the stenting resulted in successful dilatation of the Cx and she was discharged at the fifth day of intervention without any complication.